Chemical Profile and Bioactivity Evaluation of Salvia Species from Eastern Europe - Simon Vlad Luca; Krystyna Skalicka-Woźniak; Cosmin-Teodor Mihai; Adina Catinca Gradinaru; Alexandru Mandici; Nina Ciocarlan; Anca Miron; Ana Clara Aprotosoaie (MDPI AG, 2023)
The Salvia genus comprises about 1000 species endowed with medicinal, aromatic, cosmetic, and ornamental applications. Even though the genus is one of the most-studied taxa of the Lamiaceae family, data on the chemical composition and biological properties of certain locally used Salvia species are still scarce. The present work aimed to evaluate the phytochemical profile and antimicrobial, antioxidant, and cytotoxic potential of ten Salvia species that grow in Eastern Europe (e.g., the Republic of Moldova). LC-HRMS/MS metabolite profiling allowed for the annotation of 15 phenolic and organic acids, 18 flavonoids, 19 diterpenes, 5 sesterpenes, and 2 triterpenes. Multivariate analysis (e.g., principal component analysis, hierarchical cluster analysis) revealed that S. austriaca, S. nutans, and S. officinalis formed individual clusters, whereas the remaining species had a similar composition. S. officinalis showed the highest activity against Staphylococcus aureus and Streptococcus pneumoniae (MIC = 0.625 mg/mL). As evaluated in DPPH, ABTS, and FRAP assays, S. officinalis was one of the most potent radical scavenging and metal-reducing agents (CE50 values of 25.33, 8.13, and 21.01 μg/mL, respectively), followed by S. verticillata, S. sclarea, S. kopetdaghensis, S. aethiopis, and S. tesquicola. Pearson correlation analysis revealed strong correlations with rosmarinic acid, luteolin-O-glucuronide, and hydroxybenzoic acid. When the cytotoxic activity was evaluated in human breast carcinoma MCF-7 and MDA-MB-231 cells, no significant reduction in cell viability was observed over the concentrations ranging from 25 and 100 μg/mL. The results confirm the potential use of understudied Salvia species as promising sources of antioxidant compounds for developing novel pharmaceutical, nutraceutical, or cosmeceutical products.